Enhancing H2 yield through NiO loading and process optimization in CO2–CH4 reforming over fibrous silica-ceria catalysts - M.B. Bahari; A.A. Jalil; M.Y.S. Hamid; C.H. Sheng; N.S. Hassan; A.H. Hatta; N.M. Izzudin; M.H. Sawal; A.F.I. Ja’afar; M.A. Aziz (Elsevier Ltd., 2025)
The emerging global concern over climate change and the need for sustainable energy has led to extensive investigations into CO2–CH4 reforming as an efficient strategy for H2 generation. Due to numerous challenges related to catalytic activity, this study focuses on the synthesis of NiO-impregnated fibrous silica–ceria (FSCe) support, generated through a microemulsion technique. The tests revealed that the 10 %Ni/FSCe catalyst exhibited the highest CO2 (81.9–93.6 %) and CH4 (92.9–99.6 %) conversion, as well as H2 yield (46.7–58.9 %) across a temperature range of 500–800 °C, superior to the 5 %Ni/FSCe and 15 %Ni/FSCe. This is attributed to the great distribution of NiO on the FSCe support, preserving its fibrous morphology and maximizing the availability of active sites. XRD and FESEM confirm that NiO particles are well-dispersed, with no significant particle growth. CO2-TPD analysis reveals that the 10 %Ni/FSCe catalyst has a favorable distribution of basic sites, particularly Lewis basic sites, which are crucial for CO2 activation during the reforming process. Additionally, response surface methodology (RSM) was applied to the outperformed catalyst to optimize reaction conditions, identifying the ideal parameters for maximum H2 yield (41.3 %). The experimental results closely match predicted values, thus validating the optimization model and confirming the high potential for sustainable H2 production via CO2–CH4 reforming.